Emerging drugs for levodopa-induced dyskinesia. (September 2014) - Al Dakheel, Amaal; Beaulieu-Boire, Isabelle; Fox, Susan H
<x xml:space="preserve">Abstract</x> Introduction: Levodopa continues to be the main symptomatic therapy for clinical features of Parkinson's disease. However, prolonged use leads to motor complications, including levodopa-induced dyskinesia (LID). This has debilitating impact on the patients and is a significant challenge for the treating physician. There are currently limited pharmacological options for reducing established LID without causing side effects. Drugs to prevent or delay LID are also an increasing part of the strategy to manage LID, but have yet to show promise. Agents that allow levodopa to be used effectively, without inducing LID, are the goal of current research strategies. Areas covered: LID occurs due to significant modifications in the basal ganglia circuitry, probably related to the chronic, pulsatile stimulation of striatal dopaminergic receptors by levodopa, as well as altered non-dopaminergic neurotransmitter system signaling pathways. Novel treatments that either result in continuous dopaminergic receptor stimulation, levodopa 'sparing strategies' or non-dopaminergic targets, including glutamatergic, serotonergic, adenosine, adrenergic and cholinergic neurotransmission are thus the main treatment options and the focus of this manuscript. Randomized controlled trials in progress (ClinicalTrials.org) or recently published articles are included. Expert opinion: The success of future therapeutic approaches will depend on the potential success of translational research.